Femur-tibia angle and patella-tibia angle: new indicators for diagnosing anterior cruciate ligament tears in magnetic resonance imaging - Zeng Li; Mengyuan Li; Yan Du; Mo Zhang; Hai Jiang; Ruiying Zhang; Yuanchen Ma; Qiujian Zheng (BMC Sports Science, Medicine and Rehabilitation, 2022)
Abstract Background Femur-tibia angle (FTA) and patella-tibia angle (PTA) are two MRI measurements that reflect the rotation of the knee joint. The purposes of this study were to assess whether FTA and PTA are associated with ACL tear and to explore their roles in ACL tear diagnosis. Methods FTA, PTA, ACL angle and anterior tibial subluxation were compared between the two matched groups: ACL tear group and control group (each n = 20). Diagnostic performance was evaluated in a consecutive 120-patient cohort who underwent MR imaging of the knee and subsequently had arthroscopy. Different measurements were assessed by area under the curve (AUC) of receiver operating characteristic (ROC) curve. Results FTA and PTA increased significantly in ACL tears group when compared to the control group (4.79 and 7.36 degrees, respectively, p < 0.05). In distinguishing complete ACL tear, ACL angle had the highest AUC of 0.906 while AUC of PTA and FTA were 0.849 and 0.809. The cutoff of FTA was 80 degrees with a sensitivity of 82% and specificity of 68%, while the cutoff of PTA was 91 degrees with a sensitivity of 82% and specificity of 74%. In distinguishing partial ACL tear, FTA and PTA had the highest AUCs of 0.847 and 0.813, respectively. The calculated cutoff of FTA was 84 degrees with a sensitivity of 90% and specificity of 81%, while the cutoff of PTA was 92 degrees with a sensitivity of 80% and specificity of 77%. Conclusion FTA and PTA increased when ACL tears and they might be valuable in diagnosing ACL tears, especially in distinguishing partial ACL tear from intact ACL.